2019
DOI: 10.1002/pds.4904
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse drug reactions associated with ribavirin in direct‐acting antiviral therapies for chronic hepatitis C

Abstract: Purpose To identify factors associated with the development of adverse drug reactions (ADR) in ribavirin therapeutic regimens. Methods A multicenter, prospective study was conducted in three public health hospitals in Rio de Janeiro between November 2015 and March 2018. Inclusion criteria were defined by patient follow‐up at pharmaceutical consultation at the time of drug dispensing as those who used sofosbuvir in combination with simeprevir, daclatasvir, and/or ribavirin. All patients were invited to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several published studies show fatigue, headache and GI events are common with DAA treatment 47–49 . Female sex and ribavirin use were the only two predictors of having at least one adverse event in a logistic regression analysis among HCV patients treated with DAAs 50 . A pharmacovigilance study on DAAs revealed that significantly more females reported GI side effects than males 51 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several published studies show fatigue, headache and GI events are common with DAA treatment 47–49 . Female sex and ribavirin use were the only two predictors of having at least one adverse event in a logistic regression analysis among HCV patients treated with DAAs 50 . A pharmacovigilance study on DAAs revealed that significantly more females reported GI side effects than males 51 .…”
Section: Discussionmentioning
confidence: 98%
“…[47][48][49] Female sex and ribavirin use were the only two predictors of having at least one adverse event in a logistic regression analysis among HCV patients treated with DAAs. 50 A pharmacovigilance study on DAAs revealed that significantly more females reported GI side effects than males. 51 Our findings were similar to published studies in that females had a higher incidence of certain adverse events 14 and some events and laboratory findings were driven in part by ribavirin-related toxicities.…”
Section: Discussionmentioning
confidence: 99%